The Influence Of Social Media, Influencers, And Distribution On Purchase Decisions At Absolute Digital - Ayu Afridila; Harianto Harianto; Ocdy Amelia (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of social media, influencers, and distribution on purchasing decisions at Absolute Digital. This study employed a quantitative method involving 97 consumers as respondents. Data collection was conducted using a questionnaire. The data obtained were analyzed using statistical formulas, including normality tests, multicollinearity tests, heteroscedasticity tests, and multiple linear regression analysis using SPSS Version 23.0. The results of this study indicate that social media has a positive and significant effect on purchasing decisions with a t-value of 4.101 and a significance level of 0.000 < 0.05. Influencers have a positive and significant effect on purchasing decisions with a t-value of 2.644 and a significance level of 0.010 < 0.05. Distribution has a positive and significant effect on purchasing decisions with a t-value of 2.873 and a significance level of 0.005 < 0.05. Social media, influencers, and distribution simultaneously influence purchasing decisions, with an F-value of 36.628, with a significance level of 0.000 < 0.05.